2022
DOI: 10.1016/j.matpr.2021.12.503
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of masks and face shields designed by 3D printing makers; some considerations of their use against the COVID-19

Abstract: The use of mask and face shield has been established as one of the main preventive measures for the control of COVID 19 spread. In Mexico, as well as in other regions of the world, 3D printing has been employed for the design and production of masks and face shields as personal protective equipment (PPE). These models have been fabricated mainly by the makers, industries, and university communities; therefore, it is necessary to analyze the feasibility of the 3D printed PPE to understand its advantages and lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…He et al state that their structures can achieve around 79% filtration efficiency with a single layer of their material using air particulate matter in their laboratory similar to dry NaCl. Monzamodeth et al fabricated AM face masks and face shields using filament material extruded PLA to evaluate if simulating the PPE donned on mannequin head forms was possible [26] . They concluded that computational fluid dynamics (CFD) modeling was possible and that their filament printed PPE can be more efficient than home-made fabric masks, despite potential gaps in the printed layer spacing.…”
Section: Introductionmentioning
confidence: 99%
“…He et al state that their structures can achieve around 79% filtration efficiency with a single layer of their material using air particulate matter in their laboratory similar to dry NaCl. Monzamodeth et al fabricated AM face masks and face shields using filament material extruded PLA to evaluate if simulating the PPE donned on mannequin head forms was possible [26] . They concluded that computational fluid dynamics (CFD) modeling was possible and that their filament printed PPE can be more efficient than home-made fabric masks, despite potential gaps in the printed layer spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Monzamodeth et al conducted further research on 3D printed masks and explored the feasibility of different printing materials to prevent flow diffusion of human sneezing. They also considered the utilization of ethanol or commercial disinfectants to sterilize 3D printed masks [13]. The above studies provide considerable inspiration for the innovative design of masks.…”
Section: Introductionmentioning
confidence: 99%